HUBUNGAN PENGELOLAAN OBAT INSTALASI FARMASI TERHADAP KUALITAS PELAYANAN KESEHATAN DAN DAMPAKNYA TERHADAP KINERJA RSUD XYZ - Liska Marlindasari; MGS Aritonang; Tedy Herdiana (BORNEO JOURNAL OF PHARMASCIENTECH, 2020)
The implementation of Jaminan Kesehatan Nasional (JKN, National HealthInsurance) program has increased drug demand. However, a lack of inventory isknown to have caused drug stock-out that affected hospital performance. In thisdescriptive analytic study a cross sectional approach was used and 100 patientswere taken as a random sample. Primary data were obtained through structuredquestionnaire interviews and analyzed using multiple logistic regression tests. Ingeneral, the results of the study showed: 36.8% of respondents thought that thequality of Pengelolaan Obat was not good, 36.0% were doubtful about thequality of health services, and 41.0% agreed that the performance of XYZDistrict Hospital was good. Pearson's correlation test results showed there wasa relationship between Pengelolaan Obat and service quality (p <0.05, 95% CI)with procurement as the most dominant indicator (B = 1.343). In addition, thereis a relationship between service quality and performance (p <0.05, 95% CI),with physical evidence as the most dominant indicator (B = 1.299) and betweenPengelolaan Obat and performance (p <0.05, 95% CI ), with internal business(B = 1,239) and customers (B = 1,012) as the most dominant factor.